1999
DOI: 10.2307/2656789
|View full text |Cite
|
Sign up to set email alerts
|

Developmental analysis of the evolutionary origin of vegetative propagules in Mimulus gemmiparus (Scrophulariaceae)

Abstract: Mimulus gemmiparus (Scrophulariaceae), a rare endemic of Colorado, has a novel life history that depends on an unusual method of vegetative reproduction. The plants are functionally annuals; however, reproduction is asexual via propagules that have been termed gemmae. The morphological identity and the evolutionary antecedent of these propagules are unclear. We approached this problem through comparative developmental analyses of M. gemmiparus and the presumed progenitor species, Mimulus guttatus. In M. gemmip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…Plants of all populations have opposite decussate phyllotaxy with two serial axillary meristems borne in each leaf axil. The distal meristem is capable of becoming either a flower or a lateral branch; the proximate meristem typically remains quiescent (Moody et al 1999;Baker et al 2012). In general, M. guttatus in permanently wet habitats are perennial, whereas populations with temporary water availability are annual .…”
Section: Study Species and Populationsmentioning
confidence: 99%
“…Plants of all populations have opposite decussate phyllotaxy with two serial axillary meristems borne in each leaf axil. The distal meristem is capable of becoming either a flower or a lateral branch; the proximate meristem typically remains quiescent (Moody et al 1999;Baker et al 2012). In general, M. guttatus in permanently wet habitats are perennial, whereas populations with temporary water availability are annual .…”
Section: Study Species and Populationsmentioning
confidence: 99%
“…In a study of flower and bulbil development of T. oldhamii, Wang and Cronk (2003) found that a single floral meristem converts into a cluster of ca. 60-80 bulbils, unlike other bulbiliferous plants such as Polygonum viviparum and Mimulus gemmiparus, in which a single flower is replaced by a single bulbil (Diggle 1997;Moody et al 1999). As many as 20-30 clusters are produced per side branch and 20 or more branches can be present per plant (Fig.…”
Section: Introductionmentioning
confidence: 96%
“…Polygonum viviparum and Mimulus gemmiparus; Diggle 1997; Moody et al 1999) perhaps based on a common genetic mechanism in these plants. Bulbil production in such plants is often related to environmental conditions, as well as intrinsic factors such as position on the inflorescence (Diggle 1997).…”
Section: Introductionmentioning
confidence: 98%